2021
DOI: 10.1111/ajt.16565
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C–associated focal proliferative glomerulonephritis in an aviremic recipient of a hepatitis C–positive antibody donor liver

Abstract: Shortage of organs for liver transplantation (LT) and the availability of highly efficient pan‐genotypic direct‐acting antivirals (DAAs) against hepatitis C virus (HCV) have allowed the use of livers from HCV‐positive antibody/negative nucleic acid test donors (dHCV Ab+/NAT−) into aviremic HCV recipients over the last few years. We report the case of a patient who received an LT from an HCV Ab+/NAT− donor and, after HCV viremic conversion, developed a nephrotic syndrome due to a focal proliferative glomerulone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…No patients among our D+ cohort developed these. These have been occasionally described with use of other D+ organs including liver and kidney transplants, 15,16 though no cases thus far have been reported in lung recipients. Similarly, while instances of FCH have been described with other solid organ transplants, 17 none have been described for LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No patients among our D+ cohort developed these. These have been occasionally described with use of other D+ organs including liver and kidney transplants, 15,16 though no cases thus far have been reported in lung recipients. Similarly, while instances of FCH have been described with other solid organ transplants, 17 none have been described for LT.…”
Section: Discussionmentioning
confidence: 99%
“…While use of D+ livers in transplantation results in nearly universal viremia in recipients, 18 D+ lung use has had varying HCV transmission rates, from 68-100%. 12,16 Lower viral transmission rates in lung recipients is poorly understood. A lower inoculum of virus has been proposed, which may be due to lower reservoir of HCV within the lungs, and so prior work has sought to reduce transmission and viral loads in donor organs with the use of irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…These manifestations may include mixed cryoglobulinemia, non-Hodgkin lymphomas (NHL), cardiovascular disease, insulin resistance, type 2 diabetes, neurological and psychiatric diseases, and other rheumatic diseases [42]. Studies have shown that DAA treatment can improve or even resolve some EHMs associated with HCV infection [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…If recipient viremia is demonstrated, we support commencement of therapy as soon as possible, particularly in the case of non-hepatic transplantation to minimize the risk of developing fibrosing cholestatic hepatitis 3,17,18 or native renal impairment. 19,20 In general, pangenotypic regimens have been selected to reduce the risk of viral progression. The current recommendations are to complete 8 to 12 weeks of treatment in cases of HCV viremic organs transplanted into HCV uninfected recipients.…”
Section: Treatmentmentioning
confidence: 99%
“…Severe renal impairment due to acute HCV infection has also been reported in liver recipients that had delayed DAA therapy after the onset of HCV viremia. 19,20 It is notable that some clinical series have reported an increased incidence of acute cellular rejection in outcomes; however, best practices are lacking to guide transplant programs during all phases of patient care. Transplant programs developing protocols for the utilization of HCV NAT+ organs will need a multidisciplinary team to address all aspects of pretransplant and post-transplant patient care.…”
Section: Introductionmentioning
confidence: 99%